Induced polyploidization in Brassica campestris L. (Brassicaceae) - Kumar, G.; Dwivedi, K. (Цитология и генетика, 2014)
Present experimental design has been made up to obtain crop with higher ploidy level via synthetic polyploidization. Since ploidy manipulation is generally associated with the obtainment of some increased enviable traits of the crop and also provides them greater adaptability to unfavorable or harsh circumstances as compared to its diploids counterparts. Thus, herein present research autotetraploids of Brassica campestris L. have been lucratively achieved by the application of colchicine. Two methods of treatment were utilized i.e. seed treatment and seedling treatment. No polyploidy could be obtained through seed treatment while seedling treatment responded well towards polyploidy. However, the status of autotetraploidy has been confirmed by cytomorphological investigations of treated plants as against its diploids counterparts. For the purpose, morphological parameters such as increased stomata size, pollen diameter, flower size, reproductive organs whereas reduction in plant height, leaf length, leaf breadth, stomata frequency, number of flowers/inflorescence etc. were appraised. Further, cytological observations were made that had clearly revealed the doubling of genome in the autotetraploids as compared to diploids. Meanwhile, pollen fertility and size of pollen grains were evaluated as well. Разработана экспериментальная схема получения сельскохозяйственных культур с более высокой плодиностью путем искусственной полиплоидизации. Изменение плоидности обычно связано с приобретением некоторых важных признаков у таких культур, а также обеспечивает их более высокую приспособляемость к неблагоприятным или суровым условиям внешней среды по сравнению с диплоидными аналогами. В настоящем исследовании представлено успешное получение автотетраплоидов Brassica campestris L. с помощью колхицина. Для этого применяли два метода обработки – семян и проростков. Никакой полиплоидии не обнаружено при обработке семян, тогда как после обработки проростков полиплоиды были получены. С помощью цитоморфологических исследований подтверждено наличие автотетраплоидности у обработанных растений по сравнению с их диплоидными аналогами. Для этого оценивали такие морфологические параметры, как увеличенные размер устьиц, диаметр пыльцы, размер цветка, репродуктивные органы, а также уменьшенные высота растений, длина листа, ширина листа, частота устьиц, число цветков и соцветий. Более того, в результате цитологических исследований четко установлено удвоение генома у автотетраплоидов по сравнению с диплоидами. Наряду с этим в работе оценивали фертильность пыльцы и величину пыльцевых зерен.